FAKTOR PENENTU KEBERHASILAN IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA SEMARANG - Daffa Athallah, Air Langga; Hamdi, Muchlis; Rahmah, Mutia (Fakultas Politik Pemerintahan IPDN, 2024)
Abstract Waste has become one of the main challenges faced by several cities in Indonesia today. Rapid population growth significantly contributes to the increase in waste volume. The mismatch between waste production and management capacity, along with limited land availability, demands an effective management system to reduce the amount of waste generated. This study aims to identify the factors causing the suboptimal implementation of waste management policies in Semarang City and to formulate steps to enhance the success of their implementation. The approach used in this study is post-positivist, with data collection methods including interviews and documentation. The study results revealed that the factors causing the lack of successful implementation include the suitability of the instrument policy, clarity of the design policy related to procedures, time, and resources, and changes in management targets, as well as clarity of institutional structures and coordination between organizations. In addition, smooth supervision by related agencies and the high benefits felt by the community are also positive factors. On the other hand, the challenges faced include difficulties implementing policy instruments, lack of community supervision, limited resources, inability to implement standard operating procedures, and low community participation. Steps that can be taken include using human resources as human resources and the use of available technology, as well as the involvement of the community, communities, environmentalists, and the private sector in supporting the implementation of waste management policies in the city of Semarang. Keywords: Public Policy, Policy Implementation, Waste Management.